Evaluation of the role of water-shale-gas reactions on CO2 enhanced shale gas recovery. (November 2018) - Liu, Danqing; Li, Yilian; Yang, Sen
Abstract: CO2 enhanced shale gas recovery technology is promising in addressing global energy crisis as well as climate change by realizing the natural gas production and CO2 geological storage at the same time. The injection of acid CO2 into the gas-bearing shale will induce the CO2 -water-rock reactions. To explore the impact of CO2 -water-shale reactions on the shale gas recovery and CO2 storage potential, a simplified 2D reactive transport model was established. Results show that the geochemical reaction plays an important role in determining the feasibility of CO2 enhanced shale gas recovery by influencing the shale gas recovery ratio and the formation conductivity. It is suggested to include the geochemical effect in the future study of CO2 injection in shale reservoirs.